Genomic analysis of SARS-CoV-2 omicron sublineage BA.5.2.1 in Erbil/Iraq: BA.5.2.1 strain genomic analysis as a new wave in Erbil/Iraq - Majed, Sevan Omer; Jalal, Paywast Jamal; Fatah, Mohammed Hassan; Karim, Karzan Khawaraham; Karim, Abdulkarim Yasin; Miasko, Monika; Hasannajad, Sahar; Mustafa, Suhad Asaad (Cellular and Molecular Biology, 2023)
Due to several mutations in its genomic sequence, particularly in the spike protein region, the recently-discovered SARS-CoV-2 variant B.5.2.1 has alarmed health policy authorities worldwide. The World Health Organization (WHO) has labelled it "Omicron" and classified it as a worldwide variant of concern (VOC). Following the appearance of Omicron in Iraq, new cases were also detected and analyzed in Kurdistan regions. Two hundred patients were recruited in this study from Erbil/Iraq. The RNA genome samples were extracted, the qRT-PCR performed, and 10 samples were sequenced. The sample sequence was published (EPI ISL 15921492) in the GISAID international gene bank for COVID-19. When compared to the BA.1 Omicron sublineage, 17 new mutations and five deletions in the Omicron subvariant BA.5.2.1 sequence were detected. The spike region includes eight of these variations and one deletion. Overall, 30 substitutions were shared between those previously seen in the BA.1 sublineage and the newly-detected BA.5.2.1 Omicron subvariant. We detected eight new substitutions in our BA.5.2.1 subvariants (T112I, A27S, V213G, T376F, D405N, R408S, L452R, F486V), which were not mentioned previously, should be cause for concern and may be related to immune escape or viral oligomerization. Omicron might be more immune-escape-capable than the current VOCs/VOIs. However, the predicted mutational research shows no conclusive evidence that the Omicron variant may be more virulent or fatal than other variations, including Delta. The greater capacity for immunological evasion may cause the current increase in Omicron cases in Erbil/Iraq.